The Berkeley-Haas School of Business : codifying, embedding, and sustaining culture (B) - Chatman, Jennifer; Lyons, Richard K. (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2019)
The case discusses the ten initiatives implemented by the Berkeley Hass School of Business to ensure that the Business School's focus on a culture of excellence continues after the current Dean of the Hass School of Business, Richard Lyons steps down. Students are asked to consider, which processes will be most successful in sustaining the culture first implemented by the former dean Richard Lyons.
Originally Published InChatman, J. A., & Lyons, R. K. (2019). The Berkeley-Haas School of Business: Codifying, Embedding, and Sustaining Culture (B). The Berkeley-Haas Case Series. University of California, Berkeley: Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Walter A. Haas School of Business (University of California, Berkeley) -- Case studies; Universities and colleges -- California -- Berkeley -- Administration -- Case studies